Towards quantitative and multiplexed in vivo functional cancer genomics. Issue 12 (December 2018) - Winters, Ian; Murray, Christopher; Winslow, Monte
Abstract Large-scale sequencing of human tumours has uncovered a vast array of genomic alterations. Genetically engineered mouse models recapitulate many features of human cancer and have been instrumental in assigning biological meaning to specific cancer-associated alterations. However, their time, cost and labour-intensive nature limits their broad utility; thus, the functional importance of the majority of genomic aberrations in cancer remains unknown. Recent advances have accelerated the functional interrogation of cancer-associated alterations within in vivo models. Specifically, the past few years have seen the emergence of CRISPR–Cas9-based strategies to rapidly generate increasingly complex somatic alterations and the development of multiplexed and quantitative approaches to ascertain gene function in vivo. CRISPR–Cas genome editing and next-generation sequencing are driving advances in cancer modelling and functional cancer genomics. Their application to autochthonous mouse models of human cancer to generate and analyse multiplexed and/or combinatorial alterations in vivo is reviewed here.